(untitled) (Al-Academy, 2025)
The idea and philosophy of flexible systems and their effectiveness in the field of interior design came as one of the important influential points to confront future developments and to lay the foundations for achieving all functional and aesthetic requirements through the possibility of change, and the university system is one of the systems most affected by these changes. Through the preliminary exploratory study of such spaces, it was revealed that there is no identification of the influence of context. The functional and spatial pattern of these buildings depends on the degree of influence of these characteristics. Also, previous studies did not provide a clear definition of the characteristics that are most exciting in the flexibility of buildings in a way that meets the designer’s need for use in future designs and the possibility of evaluating the flexibility of building spaces from their initial plans. Due to the lack of a unified and effective flexible design system in university buildings, the research problem was defined through the following question: What is Applications of flexible systems and how effective are they in achieving the principles of design flexibility in designing the interior spaces of university buildings? The importance of the research was embodied in clarifying the idea of flexible systems to employ aesthetic values in the design of interfaces by highlighting the trends of modern systems and the extent of their effectiveness in achieving technical integration and its role in design. The goal of the research included identifying the appearance characteristics of the elements and the aesthetic foundations of flexible organization, in accordance with the requirements of the design process. In order to achieve integration with the building’s functional, environmental and formal systems by shedding light on the trends of modern systems and the extent of their effectiveness in interior spaces. The second chapter includes the theoretical framework with its discussions on flexible systems in design. The second section includes flexible systems and their effectiveness in the design of interior spaces, up to To the third chapter, with its methodology and boldness. As for the fourth chapter, one of the most important results was that the flexible systems were achieved through the effectiveness of light, its type, intensity, and formal arrangements with the proportionality of the height of the ceilings and the light and dark spaces in the internal spaces of the model. As for the most important conclusions, there is a clear difference in standards in employing flexible systems for the elements. The design of the interior spaces and their relationship to the external façade within its integrated unit in addressing the design determinants, and the multi-functional technique is used to save space and volume by achieving multi-functional furniture and by integrating space elements (staircase, partition, window, door with furniture units). And to obtain hidden storage units. By combining them with space elements and furniture units.